Natural ocean acidification at Papagayo upwelling system (north Pacific Costa Rica): implications for reef development - Sánchez Noguera, Celeste (2018)
Numerous experiments have shown that ocean acidification impedes coral calcification, but knowledge about in situ reef ecosystem response to ocean acidification is still scarce. Bahía Culebra, situated at the northern Pacific coast of Costa Rica, is a location naturally exposed to acidic conditions due to the Papagayo seasonal upwelling. We measured pH and pCO2 in situ during two non-upwelling seasons (June 2012, May–June 2013), with a high temporal resolution of every 15 and 30 min, respectively, using two Submersible Autonomous Moored Instruments (SAMI-pH, SAMI-CO2). These results were compared with published data from the 2009 upwelling season. Findings revealed that the carbonate system in Bahía Culebra shows a high temporal variability. Incoming offshore waters drive intra- and interseasonal changes. Lowest pH (7.8) and highest pCO2 (658.3 µatm) values measured during a cold-water intrusion event in the non-upwelling season were similar to those minimum values reported from upwelling season (pH = 7.8, pCO2 = 643.5 µatm), unveiling that natural acidification also occurs sporadically in the non-upwelling season. This affects the interaction of photosynthesis, respiration, calcification and carbonate dissolution and the resulting diel cycle of pH and pCO2 in the reefs of Bahía Culebra. During the non-upwelling season, the aragonite saturation state ( a) rises to values of > 3.3 and during the upwelling season falls below 2.5. The a threshold values for coral growth were derived from the correlation between measured a and coral linear extension rates which were obtained from the literature and suggest that future ocean acidification will threaten the continued growth of reefs in Bahía Culebra. These data contribute to building a better understanding of the carbonate system dynamics and coral reefs’ key response (e.g., coral growth) to natural low-pH conditions, in upwelling areas in the eastern tropical Pacific and beyond.